2021
DOI: 10.7554/elife.66192
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell analysis of mosquito hemocytes identifies signatures of immune cell subtypes and cell differentiation

Abstract: Mosquito immune cells, known as hemocytes, are integral to cellular and humoral responses that limit pathogen survival and mediate immune priming. However, without reliable cell markers and genetic tools, studies of mosquito immune cells have been limited to morphological observations, leaving several aspects of their biology uncharacterized. Here, we use single-cell RNA sequencing (scRNA-seq) to characterize mosquito immune cells, demonstrating an increased complexity to previously defined prohemocyte, oenocy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 99 publications
3
60
1
Order By: Relevance
“…this subset of PPO genes was significantly upregulated, while AgPGE2R-silencing significantly reduced their expression, supporting the novel contributions of PGE2 signaling on a subset of PPOs. Recent studies have also demonstrated that the expression of PPO1, -3, and -8 is mediated by the transcription factor lozenge ( 22), an integral regulator of oenocytoid (or comparable Drosophila crystal cell) differentiation (22,43,44), however our initial experiments suggest that lozenge expression is not directly influenced by PGE2 signaling. In addition, the regulation of a subset of PPOs via PGE2 signaling further highlight differences in gene regulation between PPO genes expressed in oenocytoids (PPO1, -3, -7 and -8) and granulocytes (PPO2, -4, -5, -6, -9) (14,22), providing support for distinct mechanisms of PPO regulation in mosquito immune cell populations that require further study.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…this subset of PPO genes was significantly upregulated, while AgPGE2R-silencing significantly reduced their expression, supporting the novel contributions of PGE2 signaling on a subset of PPOs. Recent studies have also demonstrated that the expression of PPO1, -3, and -8 is mediated by the transcription factor lozenge ( 22), an integral regulator of oenocytoid (or comparable Drosophila crystal cell) differentiation (22,43,44), however our initial experiments suggest that lozenge expression is not directly influenced by PGE2 signaling. In addition, the regulation of a subset of PPOs via PGE2 signaling further highlight differences in gene regulation between PPO genes expressed in oenocytoids (PPO1, -3, -7 and -8) and granulocytes (PPO2, -4, -5, -6, -9) (14,22), providing support for distinct mechanisms of PPO regulation in mosquito immune cell populations that require further study.…”
Section: Discussionmentioning
confidence: 55%
“…This is in agreement with recent single-cell RNA-seq analysis of An. gambiae immune cell populations (22). However, our experiments demonstrate that AgPGE2R is unaffected by phagocyte depletion, suggesting that AgPGE2R expression in oenocytoids is responsible for the majority of its expression.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations